A Comparative Analysis of Economic Growth-Inequality Nexus Across Financial Systems - Safin, Biruni Ahmad; Bintoro, Nugroho Suryo (Islamic Economics and finance in Focus, 2026)
Inequality is still a global issue. World inequality is represented by the G20 as a representation of the world economy. According to Kuznetz's theory, economic growth is the main factor that affects poverty which can be positive or negative. However, previous research has only examined Kuznetz's theory in one financial system. This study examines Kuznetz's Theory for G20 countries which are divided into three categories of financial systems, namely Sharia, Dual Banking, and Conventional. Economic growth is influenced by many things and is only sufficient for transportation, poverty distribution, PMA, GDP per capita, and labor. The study used a panel regression method for conventional and dual categories. The study uses a simple regression method for sharia. Our results show that in the conventional category, the variables of FDI and economic growth have a negative effect on inequality and the variables of labor and poverty have a negative effect on inequality. For the dual banking category, the variables of poverty and economic growth have a negative effect on inequality. For the Islamic banking category, only poverty has a negative effect on inequality. However, this is because the sample in sharia countries has become more equal in itself .